Serial changes in morphology and biochemical markers in platelet preparations with storage - Ashish Jain; Neelam Marwaha; Ratti Ram Sharma; Jyotdeep Kaur; Manish Thakur; Hari Krishan Dhawan (Asian Journal of Transfusion Science, 2015)
Background: This study was designed to perform serial assessment of alterations in platelet (PLT) count, morphology and biochemical markers of PLT activation during storage of platelet concentrates (PCs) and to correlate morphological changes with these activation markers. Materials and Methods: Our study included the platelet-rich plasma (PRP)-PC and buffy coat reduced PC (BC-PC) prepared from whole blood (WB) donations and the apheresis platelets (AP-PC). Routinely evaluated in vitro PLT parameters were followed. Morphology score (MS) was performed using the light microscopy, glucose and lactate concentration and soluble P-selectin (sP-selectin) level were determined using commercial kits. Results: The fall in mean pH from day 0 to the last day of storage was significant (P < 0.001) in all the groups. Glucose utilization was less in PRP-PC prepared from WB donations at Blood Donation Centre [PRP-PC (BDC)] when compared to PRP-PC prepared from WB donations at mobile blood drives [PRP-PC (M)] and BC-PC. Lactate accumulation was almost similar in these groups on day 3 of storage, but it was significantly lower in the AP-PC (67.54 mg/dl) except on day 5. The deterioration in MS (out of 200) was similar for PRP-PC and BC-PC on day 3 (145/144 and 145 respectively), whereas the AP-PC had a score of 161 and 147 on days 4 and 5 respectively. sP-selectin level was significantly higher in PRP-PC (BDC) in comparison to BC-PC (P = 0.001) from day 1 to day 3 and in AP-PC it was not so high (P = 0.067) even on day 5. A negative correlation existed between the MS and sP-selectin level on all days of storage within each group of PC (r = −0.351; P < 0.001) and a positive correlation was found between the MS and pH from day 0 to day 3 (r = 0.680; P = 0.004). Conclusion: The AP-PCs are superior to the BC-PC and PRP-PC with respect to in vitro quality control parameters, morphological changes and biochemical markers of PLT activation. The PRP-PCs prepared from WB donations at outstation exhibiting more rapid changes should be utilized earlier for transfusion.